Bioactive Peptide F2d Isolated from Rice Residue Exerts Antioxidant Effects via Nrf2 Signaling Pathway. (29th September 2021) - Liu, Jinliang; Wu, Qiang; Yang, Tao; Yang, Feiyan; Guo, Tianyi; Zhou, Yaping; Han, Shuai; Luo, Yi; Guo, Ting; Luo, Feijun; Lin, Qinlu
Abstract : Studies have shown that the peroxidation caused by oxygen free radicals is an important reason of vascular endothelial dysfunction and multiple diseases. In this study, active peptides (F2ds) were isolated from the fermentation product of rice dregs and its antioxidant effects were approved. Human umbilical vein endothelial cells (HUVECs) stimulated by H2 O2 were used to evaluate the antioxidation effect and its molecular mechanism in the oxidative stress model. F2d protected H2 O2 -induced damage in HUVECs in a dosage-dependent manner. F2d can reduce the expression of Keap1, promote the expression of Nrf2, and activate the downstream target HO-1, NQO1, etc. It means F2d can modulate the Nrf2 signaling pathway. Using Nrf2 inhibitor ML385 to block the Nrf2 activation, the protective function of F2d is partially lost in the damage model. Our results indicated that F2d isolated from rice exerts antioxidant effects via the Nrf2 signaling pathway in H2 O2 -induced damage, and the work will benefit to develop functional foods.